2013
DOI: 10.1016/j.chemosphere.2012.12.078
|View full text |Cite
|
Sign up to set email alerts
|

The component of Carica papaya seed toxic to A. aegypti and the identification of tegupain, the enzyme that generates it

Abstract: As Aedes aegypti transmits the etiologic agents of both yellow and dengue fever; vector control is considered essential to minimise their incidence. The aim of this work was to identify the component of Carica papaya seed toxic to A. aegypti, and the identification of tegupain, the enzyme that generates it. Aqueous extracts (1%, w/v) of the seed tegument and cotyledon of C. papaya are not larvicidal isolately. However, a mixture of 17μgmL(-1) tegument extract and 27μgmL(-1) cotyledon extract caused 100% larval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Controlling A. aegypti larvae and adults and Culex quinquefasciatus larvae using extract of C. papaya seed is due to inhibition of amylase, which reduces life span and fecundity in adults, as well as provoking mortality in larvae. 20 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…Controlling A. aegypti larvae and adults and Culex quinquefasciatus larvae using extract of C. papaya seed is due to inhibition of amylase, which reduces life span and fecundity in adults, as well as provoking mortality in larvae. 20 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…Carica papaya leaves, seeds, roots and unripe pulp, have been studied for their medicinal value such as, to treat dengue fever [ 1 , 2 ] and ulcer [ 3 ]; as antidiabetic and antioxidant [ 4 ], antitumor and immunomodulatory [ 5 ], wound healing [ 6 ], and antimicrobial agents [ 7 , 8 ]. In relation to treat dengue, C. papaya leaf extract was also found to improve thrombocyte counts both in human [ 1 ] and murine animal model [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1] Another study reported that in in vitro models, papaya leaves demonstrated significant inhibition of hemolysis. [2] A third study in mice revealed significant increase in thrombocyte counts compared to the controls.…”
mentioning
confidence: 99%